Audiência pública em Manaus: Instrumento democrático ou rito burocrático - Rodrigues, Renato Nunes (2020)
The Public Hearing, as an instrument of popular participation, is enshrined in the Brazilian Federal Constitution of 1988 and regulated through laws that list the circumstances and the respective obligation under which governments must make use of this participation device. Therefore, it contains the purpose of calling the population to the place of debate, the construction and deliberation of actions that involve the collective, thus giving the citizen the possibility of being part of governance together with the public power, a concomitant action between democracy representative democracy and deliberative democracy. This qualitative research made use of bibliographic research on the theme of critical discourse analysis in order to support the critical analysis of this instrument when investigating its practical functioning based on three criteria: speech control and shift change, use appropriate language by the audience organizers and the occurrence of deliberations. For this, it was also used the observation in loco in four distinct Public Hearings that took place in the city of Manaus and the reconstruction of a brief history of the socio-political configuration of the Brazilian society in order to give basis to an understanding that realizes whether the Public Hearing has been used in the perspective of a democratic instrument or bureaucratic rite.